TENUNAN KEDANG SEBAGAI KONTEN DAN MEDIA PEMBELAJARAN MATEMATIKA GUNA MEMBENTUK PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Gregorius Sebo Bito; Fredy Fredy; M Yazid (Program Studi PGSD Universitas Flores, 2023)
This study aims to explore the content and media for learning mathematics in woven fabrics of the Kedang community on Lembata Island, East Nusa Tenggara in order to form a profile of Pancasila students in elementary schools. The research method used is descriptive qualitative with an ethnographic approach. The object of research is Kedang woven fabric. Data collection is done through observation and documentation. Source triangulation technique is used to obtain data validity. The data analysis technique starts from the presentation, reduction and conclusion. The results of the exploration show that the mathematical content of the Kedang woven fabric is dominated by the concept of cardinal/count numbers, the concept of addition and the concept of multiplication. Apart from that, the motifs are dominated by primitive geometric shapes such as points, lines and angles, parallel lines, squares, rectangles, triangles and combinations of flat shapes. From the media side, the Kedang woven fabric motif can be used as a semi-concrete model for learning the concept of numbers, the concept of addition and multiplication, the concept of primitive geometry, the concept of parallel lines, the concept of symmetry and the concept of area. Through learning mathematics that explores the weaving in learning, students are expected to be able to maintain their noble culture, locality and identity, and remain open-minded in interacting with other cultures. Students are expected to be able to recognize and appreciate culture, intercultural communication skills in interacting with others, and reflect on and be responsible for the experience of diversity.